2006
DOI: 10.1074/jbc.m508892200
|View full text |Cite|
|
Sign up to set email alerts
|

MyD88 Adapter-like (Mal) Is Phosphorylated by Bruton's Tyrosine Kinase during TLR2 and TLR4 Signal Transduction

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
120
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(120 citation statements)
references
References 36 publications
0
120
0
Order By: Relevance
“…For instance, myristoylation and serine phosphorylation of TRAM is important for its membrane anchoring and signaling (56,57). LPS triggers tyrosine phosphorylation of MyD88 (60), and tyrosine phosphorylation of Mal has been reported to be important for TLR2 and TLR4 signaling (55). Non-classical Lys-63 ubiquitination of TRAF-6, necessary for induction of its functional activities, is another example of posttranslational modifications of adapters (61).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, myristoylation and serine phosphorylation of TRAM is important for its membrane anchoring and signaling (56,57). LPS triggers tyrosine phosphorylation of MyD88 (60), and tyrosine phosphorylation of Mal has been reported to be important for TLR2 and TLR4 signaling (55). Non-classical Lys-63 ubiquitination of TRAF-6, necessary for induction of its functional activities, is another example of posttranslational modifications of adapters (61).…”
Section: Discussionmentioning
confidence: 99%
“…pEFBOS-His/ FLAG-human MD-2 was provided by Dr. Kensuke Miyake (Research Institute for Microbial Diseases, Osaka University, Osaka, Japan). pEFBOS-FLAG-Mal WT and P125H mutant, pDC304-HA-Mal, pCDNA3-YFP-MyD88, pCDNA3-Btk, pCDNA3-Myc-IRAK-2, and pRK5-FLAG-TRAF-6 were described previously (27,51,55). pFLAG-CMV-1 encoding WT CD4-TLR4 was kindly provided by Dr. Stephen T. Smale (Howard Hughes Medical Institute, UCLA, Los Angeles, CA), and pRL-TK-Renilla luciferase was from Promega.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested a linkage of TLRs and tyrosine kinases, including Syk via MyD88-STAP-2 interaction (51) and Btk via direct interaction with TIR domain (52), both of which have been shown to activate PLC␥ isoforms. Moreover, Btkinduced phosphorylation of TIRAP/Mal has recently been reported to play an important role in TLR signal transduction (53), which may occur at a phosphatidylinositol diphosphaterich membrane compartment after recruitment of MyD88 to membrane-localized TIRAP/Mal (54). A schematic of signaling pathways proposed here is shown in Fig.…”
Section: Volume 282 • Number 11 • March 16 2007mentioning
confidence: 99%